Genome Sequence Analysis and Characterization of Shiga Toxin 2 Production by Escherichia coli O157:H7 Strains Associated With a Laboratory Infection - Eppinger, Mark; Almería, Sonia; Allué-Guardia, Anna; Bagi, Lori K.; Kalalah, Anwar A.; Gurtler, Joshua B.; Fratamico, Pina M. (Frontiers in Cellular and Infection Microbiology, 2022)
A laboratory-acquired E. coli O157:H7 infection with associated severe sequelae including hemolytic uremic syndrome occurred in an individual working in the laboratory with a mixture of nalidixic acid-resistant (NalR) O157:H7 mutant strains in a soil-biochar blend. The patient was hospitalized and treated with an intravenous combination of metronidazole and levofloxacin. The present study investigated the source of this severe laboratory acquired infection and further examined the influence of the antibiotics used during treatment on the expression and production of Shiga toxin. Genomes of two Stx2a-and eae-positive O157:H7 strains isolated from the patient’s stool were sequenced along with two pairs of the wt strains and their derived NalR mutants used in the laboratory experiments. High-resolution SNP typing determined the strains’ individual genetic relatedness and unambiguously identified the two laboratory-derived NalR mutant strains as the source of the researcher’s life-threatening disease, rather than a conceivable ingestion of unrelated O157:H7 isolates circulating at the same time. It was further confirmed that in sublethal doses, the antibiotics increased toxin expression and production. Our results support a simultaneous co-infection with clinical strains in the laboratory, which were the causative agents of previous O157:H7 outbreaks, and further that the administration of antibiotics may have impacted the outcome of the infection.